(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The Holy Indian science of Ayurveda is one of the master stroke in Research field in todays era. The holy science still needs the research in its most areas & in a proper way. There are most of the topics & concepts in Ayurveda that has to be elaborated & deeply studied. Garbha sharir is one such topic that holds importance. It is been described properly in Sharirsthana of Samhitas. Charaka says that Shukra, Shonita & Jeeva comes together to form Garbha. The best thing of Ayurveda is that the concept of beeja, embryology that is Garbhavakranti & concept of fertilization that is Garbhadhana is properly & authentically described. As its well known that Embryology deals with hereditary factors, month wise development of fetus, sex determination etc , it is very curious & interesting phenomenon to see a embryo growing inside the womb. Ayurvedic view of Garbha Sharir and modern embryology can mostly be correlated in almost all ways & aspects. The present article is a sincere effort to study the concept of Garbha sharir in Ayurveda & its exploration & proper explaination..